Trypanothione Reductase: design of a potential new class of inhibitors - Silva, Maria José dos Santos Alves da (2018)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2016